Unnegotiated Contracts of Adhesion in American Common and Civil Law Jurisdictions: The Canadian and Argentinian Cases - Francesco Delfini (Milan Law Review, 2021)
The essay addresses the control of Unnegotiated Standard Form Contracts and the legal tools developed for such purpose both in common and civil law traditions. In particular, on the one hand, it focuses on unconscionability, as it was originally crafted by the USA’s Uniform Commercial Code and recently shaped as a new doctrine by the Canadian Supreme Court; on the other hand, it looks to the American civil codes of Quebec and Argentina. Then it deals with some cases occurring in Italian case law, suggesting that the Quebec and Argentinian Codes (as well as the recently amended French Civil Code) could give guidance in assessing the enforceability of unnegotiated standard clauses that affect the very core of the contract and its subject matter.